Introduction to coaching psychology - O'Riordan, Siobhain; Palmer, Stephen (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Introduction to Coaching Psychology covers key topics including the background and development of coaching psychology, the coach-coachee relationship, coaching psychology approaches and models, and themes such as assessment, contracting and set up in coaching psychology practice"--
OCLC-licensed vendor bibliographic record.
Keywords: Personal coaching; Positive psychology; Counseling psychology; PSYCHOLOGY / Industrial & Organizational Psychology; PSYCHOLOGY / Mental Health